Molecular Cloning and Characterization of Four Genes Encoding Ethylene Receptors Associated with Pineapple (Ananas comosus L.) Flowering - Li, Yun-He; Wu, Qing-Song; Huang, Xia; Liu, Sheng-Hui; Zhang, Hong-Na; Zhang, Zhi; Sun, Guang-Ming (Frontiers in Plant Science, 2016)
Exogenous ethylene, or ethephon, has been widely used to induce pineapple flowering, but the molecular mechanism behind ethephon induction is still unclear. In this study, we cloned four genes encoding ethylene receptors (designated AcERS1a, AcERS1b, AcETR2a and AcETR2b). The 5′ flanking sequences of these four genes were also cloned by self-formed adaptor PCR and SiteFinding-PCR, and a group of putative cis-acting elements was identified. Phylogenetic tree analysis indicated that AcERS1a, AcERS1b, AcETR2a and AcETR2b belonged to the plant ERS1s and ETR2/EIN4-like groups. Quantitative real-time PCR showed that AcETR2a and AcETR2b (subfamily 2) were more sensitive to ethylene treatment compared with AcERS1a and AcERS1b (subfamily 1). The relative expression of AcERS1b, AcETR2a and AcETR2b was significantly increased during the earlier period of pineapple inflorescence formation, especially at 1-9 days after ethylene treatment (DAET), whereas AcERS1a expression changed less than these three genes. In situ hybridization results showed that bract primordia (BP) and flower primordia (FP) appeared at 9 and 21 DAET, respectively, and flowers were formed at 37 DAET. AcERS1a, AcERS1b, AcETR2a and AcETR2b were mainly expressed in the shoot apex at 1-4 DAET; thereafter, with the appearance of BP and FP, higher expression of these genes was found in these new structures. Finally, at 37 DAET, the expression of these genes was mainly focused in the flower but was also low in other structures. These findings indicate that these four ethylene receptor genes, especially AcERS1b, AcETR2a and AcETR2b, play important roles during pineapple flowering induced by exogenous ethephon.